Intelligent Autonomous Systems 15 Proceedings of the 15th International Conference IAS-15 - Strand, Marcus; Dillmann, Rüdiger; Menegatti, Emanuele; Ghidoni, Stefano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the latest advances and research achievements in the fields of autonomous robots and intelligent systems, presented at the IAS-15 conference, held in Baden-Baden, Germany, in June 2018. It brings together contributions from researchers, engineers and practitioners from all over the world on the main trends of robotics: navigation, path planning, robot vision, human detection, and robot design - as well as a wide range of applications. This installment of the conference reflects the rise of machine learning and deep learning in the robotics field, as employed in a variety of applications and systems. All contributions were selected using a rigorous peer-review process to ensure their scientific quality. The series of biennial IAS conferences was started in 1986: since then, it has become an essential venue for the robotics community.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence